Applications of Lucas Balancing Polynomial to Subclasses of Bi-Starlike Functions - Gangadharan Murugusundaramoorthy; Luminita-Ioana Cotîrlă; Daniel Breaz; Sheza M. El-Deeb (Axioms)
The Lucas balancing polynomial is linked to a family of bi-starlike functions denoted as <semantics><msubsup>Sscc</msubsup>(ϑ,Ξ(x))</semantics>, which we present and examine in this work. These functions are defined with respect to symmetric conjugate points. Coefficient estimates are obtained for functions in this family. The classical Fekete–Szegö inequality of functions in this family is also obtained.